PEMODELAN PEMILIHAN MODA DENGAN METODE STATED PREFERENCE, STUDI KASUS PERPINDAHAN DARI SEPEDA MOTOR KE BRT RUTE SEMARANG – KENDAL - Muammar Fahmi; Uum Umyati; Bambang Riyanto; Kami Hari Basuki (Jurnal Karya Teknik Sipil, 2015)
Kendal regency as satellite city of Semarang has established a mutual relationship and completing each other. The economic development and population insde the rural area of Semarang and Kendal regency has raised up since the street of Jerakah - Mijen has been widened in 2004 - 2012. This can be seen during working hour in which Semarang - Kendal road was fully filled by vehicles especially motorcycle. Based on this, the research must be done to reduce the congestion that occurs around the Semarang - Kendal. This study aims to perform modal choice modeling with stated preference methods, so that the government can take better policies to support the operation of the BRT Semarang - Kendal route. The survey was conducted by spreading the questionnaire and interview that consist of socio-economic characteristic of the respondent, route characteristic, and questionnaire that is organized through stated preference technique with additional attribute namely, the margin of route cost and margin of time used of departure between motorcycle and BRT Semarang-Kendal route. Study sites were around the Semarang - Kendal and on the bus route Semarang - Kendal. From the research result, it is shown that the choice of vehicle is based on the margin of route cost, namely UBRT – USM = 1,2353 - 0,0007 (ΔX1). Meanwhile, the choice of vehicle based on the margin of time used is UBRT – USM = 2,61336 - 0,17441 (ΔX2). In addition, the choice of transportation mode based on margin of cost and time is UBRT – USM = 2,6683 - 0,7365ΔX1 + 0,00219ΔX2. The potential of the shifting of passenger from motorcycle to BRT based on the route cost is 74%. Whereas, based of time used is 50%, and 32% is based on both choices. In addition to modeling mode choice, we need to Traffic Demand Management (TDM) are both on regular lines Semarang - Kendal, because the fundamental purpose of building a BRT route Semarang - Kendal limited only to reduce congestion caused by the use of motorcycles in bulk.